Delirium and Delirium Severity Predict the Trajectory of the Hierarchical Assessment of Balance and Mobility in Hospitalized Older People: Findings From the DECIDE Study. Issue 3 (16th March 2021) - Richardson, Sarah; Murray, James; Davis, Daniel; Stephan, Blossom C M; Robinson, Louise; Brayne, Carol; Barnes, Linda; Parker, Stuart; Sayer, Avan A; Dodds, Richard M; Allan, Louise
Abstract: Background: Delirium is common, distressing, and associated with poor outcomes. Despite this, delirium remains poorly recognized, resulting in worse outcomes. There is an urgent need for methods to objectively assess for delirium. Physical function has been proposed as a potential surrogate marker, but few studies have monitored physical function in the context of delirium. We examined if trajectories of physical function are affected by the presence and severity of delirium in a representative sample of hospitalized participants older than 65 years. Method: During hospital admissions in 2016, we assessed participants from the Delirium and Cognitive Impact in Dementia study daily for delirium and physical function, using the Hierarchical Assessment of Balance and Mobility (HABAM). We used linear mixed models to assess the effect of delirium and delirium severity during admission on HABAM trajectory. Results: Of 178 participants, 58 experienced delirium during admission. Median HABAM scores in those with delirium were significantly higher (indicating worse mobility) than those without delirium. Modeling HABAM trajectories, HABAM scores at first assessment were worse in those with delirium than those without, by 0.76 (95% CI: 0.49–1.04) points. Participants with severe delirium experienced a much greater perturbance in their physical function, with an even lower value at first assessment and slower subsequent improvement. Conclusions: Physical function was worse in those with delirium compared to without. This supports the assertion that motor disturbances are a core feature of delirium and monitoring physical function, using a tool such as the HABAM, may have clinical utility as a surrogate marker for delirium and its resolution.